Microrna as a potential biomarker in the diagnosis and prognosis of Hodgkin’s lymphoma: a systematic review - Nik Izhar, Nik Nurdiyana; Mohammad, Mardhiah; Abdul Rahman, Rozlin; Zainuddin, Norafiza (IIUM Press, 2019)
Diagnosing Hodgkin’s Lymphoma (HL) has become a challenge nowadays and mostly limited to the current therapy. Thus, microRNA is believed to exhibit the best candidate for HL diagnosis and prognosis. To assess the true value of miRNA as a biomarker in HL, a systematic review was conducted to collect and evaluate the current knowledge of miRNAs functioning as diagnostic and prognostic biomarkers in HL. A systematic literature search was conducted to retrieve relevant articles from five different electronic databases up to April 2018. Search terms included ‘Hodgkin’s lymphoma’, ‘microRNA’, ‘prognostic biomarker’ and ‘diagnostic biomarker’. The selected articles were assessed using CROWE critical appraisal tool. The literature search identified a total of 1362 articles from which a final 20 relevant studies were included. In total, 118 miRNAs with significance to HL were observed. 85 miRNAs were reported with regards to its expression and associated pathogenesis. 66 miRNAs were found to be up-regulated in HL, while 18 were found down-regulated. 20 miRNAs were correlated to prognosis. One study reported higher expression of miRNAs based on the expression in plasma extracellular vesicle, and the finding was found to be reliable for therapy response. Three top most important miRNAs were also depicted in this review, which may have significant role in HL pathogenesis. In conclusion, the relevant information on miRNAs particularly in monitoring treatment response is hoped to benefit the treatment advances in HL in the future.